Neuropsychological evidence of a third visual pathway specialized for social perception - David Pitcher (Nature Communications)
Recent evidence suggests the existence of a neural pathway specialized for social perception projecting between the well-established “what” and “where” pathways. A new study of neuropsychological patients demonstrates that this social pathway is causally essential for recognizing dynamic facial expressions.